Analysis of How Parenting Affects the Personalities of Islamic Junior High School Students in Medan, Indonesia - Aisyah, Siti; Hardjo, Suryani; Jallow, Sirajo (International Journal of Islamic Educational Psychology, 2022)
This research aims to determine how parents treat their children significantly contributes to the child’s personality. This quantitative descriptive research had a population of 5,378 students of SMP Islam Education in Medan. The research sample was 818 students. The results found that the personality dimensions of neuroticism reflected stressful, irritable, unrealistic, anxious, and restless behaviors. Authoritarian parenting style harmed neuroticism personality. In addition, a regression coefficient of 0.10 (p = 0.05) was found for openness personality. Therefore, authoritarian parenting had a positive effect on open personality. The democratic parenting variable had a regression coefficient of 0.87 (p0.001), 0.82 (p0.001), 0.57 (p0.001), and 0.56 (p0.001) for personality openness, conscientiousness, extraversion, and agreeableness. Parents are influential in developing a student’s personality because it affect emotional maturity, desire for achievement, social skills, and personal maturity related to student personality dimensions. Thus, parents must apply authoritarian parenting to discipline children, shaping them to have positive personalities.